NÅR KULTUR KOMMER I VEJEN: Kapitalmøder og kulturforståelser på en international uddannelse i Danmark - Wilken, Lisanne (Tidsskriftet Antropologi, 2007)
Over the past 10-15 years internationalisation has become a buzz word in university education. International institutions as well as national and regional governments promote international exchange of students and teachers, and universities compete to attract foreign students. Internationalisation is generally based on the idea of intercultural compatibility, which implies that ‘scholastic capital’ fairly easily can be transferred from one university context to another and that educational settings can promote and benefit from cultural diversity. With reference to a study of one internationalised educational setting in Denmark, this article explores some of the less recognised challenges in relation to internationalisation of university education. Inspired by Pierre Bourdieu’s concept of cultural capital and Gregory Bateson’s concept of framing, the article argues that the combination of differences in cultural capital and differences in locally embedded ‘context knowledge’ may produce obstacles to fruitful intercultural interaction. It argues, moreover, that the interactions between students are to a large extent based on an unequal relationship between a home-team and a foreign team rather than on an equal relationship between different nationalities. The obstacles this creates are, to a large extent, unacknowledged, because individuals tend to interpret differences as ‘national differences’.